2017
DOI: 10.15537/smj.2017.9.19864
|View full text |Cite
|
Sign up to set email alerts
|

Screening for skin-sensitizing allergens among patients with clinically suspected allergic contact dermatitis

Abstract: Objectives:To detect common skin-sensitizing agents among patients experiencing allergic contact dermatitis (ACD).Methods:This was a retrospective study of 152 patients with clinically suspected ACD who underwent patch testing in an allergy clinic at King Khalid University Hospital, Riyadh, Kingdom of Saudi Arabia between January 2012 and February 2015. Of these patients, only 74 (48%) patients reacted to one or more contact allergens. This group of patients included 58 (78.4%) women and 16 (21.6%) men (mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…In addition to metals, the other common allergens identified included thimerosal, colophony, carba mix, fragrance mix, balsam of Peru and formaldehyde. The frequency of positive patch test results in the patients (62.2%) as well as clear predominance of women among applicants with eczema, are within the range of results available in literature ( 9 , 10 ).…”
Section: Discussionsupporting
confidence: 75%
“…In addition to metals, the other common allergens identified included thimerosal, colophony, carba mix, fragrance mix, balsam of Peru and formaldehyde. The frequency of positive patch test results in the patients (62.2%) as well as clear predominance of women among applicants with eczema, are within the range of results available in literature ( 9 , 10 ).…”
Section: Discussionsupporting
confidence: 75%
“…In the study done by Watts et al 12 and Shakoor et al 21 the most common allergen was nickel sulphate like ours. However, second most common allergen in their study was PPD.…”
Section: Discussionsupporting
confidence: 57%
“…Boonchai & Iamtharachai [18] found a higher incidence of sensitivity to gold (30.7%) compared to nickel (27.6%) in their study of adults in Thailand. Shakoor et al [16] and How et al [17] also reported reasonably high incidences of sensitivity to gold in their studies on adults in Saudi Arabia (13.5%) and Malaysia (15.2%). In comparison, Fowler et al [19] reported the 9.5% of their patients with suspected contact allergy in North America had a sensitivity to gold.…”
Section: Discussionmentioning
confidence: 86%
“…There may be several reasons for this: firstly, gold is present in the TRUE Test1 panel 3 but does not feature in some other patch test series, such as the European baseline series and it is only in the last two decades that gold has really been accepted as a potentially significant allergen [15]. Finally, it may be that sensitivity to gold is more common in certain populations, such as southeast Asian and Middle Eastern populations [16][17][18], where higher rates of sensitivity to gold are reported in the literature. Boonchai & Iamtharachai [18] found a higher incidence of sensitivity to gold (30.7%) compared to nickel (27.6%) in their study of adults in Thailand.…”
Section: Discussionmentioning
confidence: 99%